Hubungan Ganguan Akibat Kekurangan Yodium (GAKY) dengan Prestasi Belajar di SDN Tanggalrejo Kecamatan Mojoagung Kabupaten Jombang - Diah Ayu Pitaloka; Mamik Ratnawati; Ida Nikmatul Ulfa (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
The Correlation Of Iodine Deficiency Disorder (IDD) With Learning Achievement At Public Ementary School ( Sdn ) Tanggalrejo Village , Mojoagung Sud District , In Jombang District. One nutritional problem In indonesia is IDD. IDD is known to be able to effect abnormality such as mumps, cretin, intelligence disorder, mental disorder and physical development disorder that affect the quality of HR (Human Resources). Impaired intelegence of child, make the child will have difficulty to achieve learning. The research aimed to understand the correlation of IDD with learning achievement at ( SDN ) Tanggalrejo Village, Mojoagung Sub district in Jombang District. This research was an analytic correlation with cross sectional approach. The population as much as 54 respondent was the students of grade 3 at Public Elementary school ( SDN ) Tanggalrejo Village Mojoagung sub district in Jombang District , and total of samples was 54 respondents with the technique of sampling used total sampling. The independent variable was Iodine deficiency Disorders(IDD) and the dependent variable was learning achievement with the instrument in the form of inspection and palpation of thyroid gland and documentation of the value with Spearman rank test. The results showed that the most (70.4%) IDD was 0 degrees and the most (33.3%) learning achievement was less , it was obtained r value = 0.351, ρ = 0.009 and ɑ = 0.05, because ρ <ɑ then Ho was refused it meant there was correlation of IDD with grade 3 student ‘s achievement at Public Elementary School (SDN ) Tanggalrejo Village , Mojoagung Sub district in Jombang District.Based on the description above, so that the increase of iodized salt consumption is needed by school-age children to prevent the emergence of new problems, and as a correction for people with IDD. And necessary counceling about the important iodized salt to community. Keywords: IDD, Learning Achievement